Responsive Microneedles as a New Platform for Precision Immunotherapy - Xinyang Liu; Haohao Song; Tairan Sun; Hai Wang (MDPI AG, 2023)
Microneedles are a well-known transdermal or transdermal drug delivery system. Different from intramuscular injection, intravenous injection, etc., the microneedle delivery system provides unique characteristics for immunotherapy administration. Microneedles can deliver immunotherapeutic agents to the epidermis and dermis, where immune cells are abundant, unlike conventional vaccine systems. Furthermore, microneedle devices can be designed to respond to certain endogenous or exogenous stimuli including pH, reactive oxygen species (ROS), enzyme, light, temperature, or mechanical force, thereby allowing controlled release of active compounds in the epidermis and dermis. In this way, multifunctional or stimuli-responsive microneedles for immunotherapy could enhance the efficacy of immune responses to prevent or mitigate disease progression and lessen systemic adverse effects on healthy tissues and organs. Since microneedles are a promising drug delivery system for accurate delivery and controlled drug release, this review focuses on the progress of using reactive microneedles for immunotherapy, especially for tumors. Limitations of current microneedle system are summarized, and the controllable administration and targeting of reactive microneedle systems are examined.